Coaxial micro-extrusion of a calcium phosphate ink with aqueous solvents improves printing stability, structure fidelity and mechanical properties. (15th April 2021) - Bagnol, Romain; Sprecher, Christoph; Peroglio, Marianna; Chevalier, Jerome; Mahou, Redouan; Büchler, Philippe; Richards, Geoff; Eglin, David
Abstract: Micro-extrusion-based 3D printing of complex geometrical and porous calcium phosphate (CaP) can improve treatment of bone defects through the production of personalized bone substitutes. However, achieving printing and post-printing shape stabilities for the efficient fabrication and application of rapid hardening protocol are still challenging. In this work, the coaxial printing of a self-setting CaP cement with water and ethanol mixtures aiming to increase the ink yield stress upon extrusion and the stability of fabricated structures was explored. Printing height of overhang structure was doubled when aqueous solvents were used and a 2 log increase of the stiffness was achieved post-printing. A standard and fast steam sterilization protocol applied as hardening step on the coaxial printed CaP cement (CPC) ink resulted in constructs with 4 to 5 times higher compressive moduli in comparison to extrusion process in the absence of solvent. This improved mechanical performance is likely due to rapid CPC setting, preventing cracks formation during hardening process. Thus, coaxial micro-extrusion-based 3D printing of a CPC ink with aqueous solvent enhances printability and allows the use of the widespread steam sterilization cycle as a standalone post-processing technique for production of 3D printed personalized CaP bone substitutes. Statement of significance: Coaxial micro-extrusion-based 3D printing of a self-setting CaP cement with water:ethanol mixtures increased the ink yield stress upon extrusion and the stability of fabricated structures. Printing height of overhang structure was doubled when aqueous solvents were used, and a 2 orders of magnitude log increase of the stiffness was achieved post-printing. A fast hardening step consisting of a standard steam sterilization was applied. Four to 5 times higher compressive moduli was obtained for hardened coaxially printed constructs. This improved mechanical performance is likely due to rapid CPC setting in the coaxial printing, preventing cracks formation during hardening process. Graphical abstract: Image, graphical abstract